The Impact of Inflation Targeting on Inflation and Growth: How Robust Is the Evidence? - Pramod N. (Raja) Junankar; Chun Yee Wong (Institute of Labor Economics (IZA), 2020)
This paper evaluates the success of Inflation Targeting on inflation and growth on a large panel data set of both developing and developed countries. Earlier studies have found contradictory results depending on the methodology used, different authors have used different estimation methods on different samples of data. Some of the differences in results may also be due to the different time periods (or different frequencies of data) used in the estimation. In this paper, we provide evidence to show that the support for a successful Inflation Targeting policy is very weak or non-existent. We use various estimation methods on panel data on a large sample of countries. We note that the results depend critically on the sample selected, the method of estimation employed, and the procedure used to control for outliers. Section 2 of the paper outlines the process by which inflation targeting is hypothesised to influence inflation and growth, Section 3 surveys this literature, and Section 4 describes the data and provides descriptive statistics comparing the performance of Inflation Targeting countries and non-Inflation Targeting countries, Section 5 uses panel estimation methods including GMM techniques on different samples of data and demonstrates the fragile nature of the results. Section 6 provides the conclusions that suggest that IT policy does not necessarily help to reduce inflation and certainly does not stimulate economic growth.
Keywords: E31; J68; J08; 330; Inflation Targeting; inflation; growth